Decline in cardiorespiratory fitness and its association with vascular aging and subclinical atherosclerosis in healthy older adults: a 3-year longitudinal study - Vincent Groesser; Christopher Weyh; Torsten Frech; Natascha Sommer; Klaus Eder; Astrid Most; Samuel Sossalla; Karsten Krüger; Pascal Bauer (GeroScience, 2026)
Aging is associated with progressive deterioration of vascular function and cardiovascular risk. Cardiorespiratory fitness (CRF) is closely associated with cardiovascular health, yet longitudinal data in healthy older adults remain limited. This study examined 3-year changes in vascular and echocardiographic parameters in older adults and their associations with CRF and muscle strength. Forty-nine participants (mean age 63.8 ± 3.8 years) underwent vascular assessments (brachial/central blood pressure (BP), pulse wave velocity (PWV), augmentation index), echocardiography, CRF testing via spiroergometry to determine VO 2 peak, muscle strength testing, and carotid sonography at baseline and after 3 years. Participants were grouped by carotid plaque status: no atherosclerosis, existing atherosclerosis, or newly developed atherosclerosis. Over 3 years, CRF and muscle strength (grip strength, leg flexion) declined significantly (all p < 0.005), while systolic BP ( p = 0.042), brachial-ankle PWV ( p = 0.006), and echocardiographic parameters including aortic root diameter and ventricular dimensions increased (all p < 0.001). Participants with newly developed atherosclerosis showed the greatest CRF decline ( p = 0.012). Changes in CRF were inversely associated with changes in systolic, diastolic, and central BP (all p < 0.01). Declines in leg flexion strength were also linked to larger BP increases. Participants maintaining > 90% of baseline VO 2 peak had significantly smaller BP increases. These results indicate that vascular aging progresses measurably within a few years in clinically healthy older adults and is associated with declines in CRF and muscle strength. Preservation of CRF is linked to more favorable vascular aging profiles and a lower prevalence of newly developed atherosclerosis. Graphical Abstract

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

The University of Oklahoma Inpatient Spine Protocol: optimizing surgical outcomes through standardized perioperative care - David Barkyoumb; William C. Kaiser; Lonnie Smith; Lance M. Villeneuve; Graham Mulvaney; Chao Li; Christopher S. Graffeo; Andrew M. Bauer; Hakeem J. Shakir; Karl Balsara; M. Burhan Janjua; John F. Burke; et al. (GeroScience, 2025)

Assessing predictors for fuel moisture content in Central European forests - Johanna Kranz; Konrad Bauer; Valerio Pampanoni; Li Zhao; Christopher Marrs; Matthias Mauder; Markéta Poděbradská; Marieke van der Maaten-Theunissen; Marta Yebra; Matthias Forkel (Agricultural and Forest Meteorology, 2025)

The Contemporary Distribution of Scincine Lizards Does Not Reflect Their Biogeographic Origin - Aniruddha Datta‐Roy; Matthew C. Brandley; Christopher C. Austin; Aaron M. Bauer; David James Harris; Salvador Carranza; Kanishka D. B. Ukuwela; Anslem De Silva; Krystal A. Tolley; K. Praveen Karanth; Maitreya Sil (Journal of Biogeography, 2025)
Aim We assess the systematic relationships and historical biogeographic patterns in the subfamily Scincinae, a group of lizards that primarily inhabits the Afro‐Madagascan and Saharo‐Arabian regions with isolated lineages in Europe, North America, East Asia, India and Sri Lanka. The contemporary distribution of these lineages on the historical Laurasian and Gondwanan landmasses make scincines an ideal system to study the roles of vicariance and dispersal on a geologic scale of tens of millions of years. Location Global. Taxon Subfamily Scincinae (Family Scincidae). Methods We conducted biogeographic analyses on a reconstructed, time‐calibrated species tree of scincine genera, including members of the other Scincidae subfamilies, using seven nuclear loci (~6 k base pairs). We also constructed a lineage‐through‐time plot to assess the timing of diversification within scincines. Results Our analysis estimated strong support for the monophyly of Scincinae that is further comprised a strongly‐supported Gondwanan clade nested within a broader Laurasian group. While most of the extant, genus‐level diversity within the Gondwanan clade was accrued post‐Eocene, the majority of the Laurasian lineages diverged during the Palaeocene or earlier, suggesting large‐scale extinctions on continents of Laurasian origin. Counterintuitively, scincines from India and Sri Lanka have distinct biogeographical origins despite a long tectonic association between these landmasses, suggesting at least two independent, long‐distance, trans‐oceanic dispersal events into the subcontinent. Our biogeographic analyses suggest that scincines likely originated in East and Southeast Asia during the late Cretaceous ( ca . 70 Ma), and eventually dispersed westwards to Africa and Madagascar, where their greatest current‐day species richness occurs. Main Conclusions Our study demonstrates the concomitant roles of dispersal and extinction in shaping modern‐day assemblages of ancient clades such as scincine lizards. Our range evolution analysis shows that despite the greater diversity observed in the Afro‐Madagascan region, the origin of scincines can be traced back to Southeast Asia and East Asia, followed by westward dispersals. These dispersals may have been followed by significant extinctions in tropical East Asia, resulting in relatively lower diversity of scincines in these regions. Notably, our analysis reveals that Sri Lankan and Peninsular Indian scincines have distinct evolutionary origins.

Regional Processes Mediate Ecological Selection and the Distribution of Plant Diversity Across Scales - Christopher P. Catano; Jonathan Bauer; Tyler Bassett; Eric Behrens; Lars A. Brudvig (Ecology Letters, 2025)
Community ecology remains focused on interactions at small scales, which limits causal understanding of how regional and local processes interact to mediate biodiversity changes. We hypothesise that species pool size and immigration are two regional processes altering the balance between local niche selection and drift that cause variation in plant diversity. We manipulated the richness and number of seeds sown (species pool size and immigration respectively) into 12 grasslands across a landscape soil moisture gradient. Greater immigration and smaller species pools increased the variation in plant composition explained by soil moisture gradients but resulted in greater erosion of plant α ‐diversity and spatial β ‐diversity over time. Our results suggest that regional constraints on colonisation make community assembly more variable but help maintain species diversity by limiting biotic homogenisation. This study provides large‐scale experimental evidence on how regional contexts can alter the relative importance of fundamental processes shaping biodiversity change across scales.

Synergistic effects of plasma S100B and MRI measures of cerebrovascular disease on cognition in older adults - Colleen Pappas; Christopher E. Bauer; Valentinos Zachariou; T. J. Libecap; Beatriz Rodolpho; Tiffany L. Sudduth; Peter T. Nelson; Gregory A. Jicha; Anika MS Hartz; Xingfeng Shao; Danny J. J. Wang; Brian T. Gold (GeroScience, 2025)
There is growing interest in studying vascular contributions to cognitive impairment and dementia (VCID) and developing biomarkers to identify at-risk individuals. A combination of biofluid and neuroimaging markers may better profile early stage VCID than individual measures. Here, we tested this possibility focusing on plasma levels of S100 calcium-binding protein B (S100B), which has been linked with blood–brain-barrier (BBB) integrity, and neuroimaging measures assessing BBB function (water exchange rate across the BBB (k w )) and cerebral small vessel disease (white matter hyperintensities (WMHs)). A total of 74 older adults without dementia had plasma samples collected and underwent cognitive assessment. A subsample had neuroimaging data including diffusion prepared pseudo-continuous arterial spin labeling (DP-pCASL) for assessment of BBB k w and T2-weighted fluid-attenuated inversion recovery (FLAIR) for quantification of WMHs. Results indicated that higher plasma S100B levels were associated with poorer episodic memory performance ( β = − .031, SE = .008, p < .001). Moreover, significant interactions were observed between plasma S100B levels and parietal lobe BBB k w (interaction β = .095, SE = .042, p = .028) and between plasma S100B levels and deep WMH volume (interaction β = − .025, SE = .009, p = .007) for episodic memory. Individuals with the poorest memory performance showed both high plasma S100B and either low BBB k w in the parietal lobe or increased deep WMH burden. Taken together, our results provide support for the combined use of biofluid and neuroimaging markers in the study of VCID.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Association of cardiorespiratory fitness level with vascular function and subclinical atherosclerosis in the elderly - Vincent Größer; Christopher Weyh; Tim Böttrich; Torsten Frech; Svenja Nolte; Natascha Sommer; Magdalena Huber; Klaus Eder; Oliver Dörr; Sophie Hoelscher; Rebecca Weber; Ebru Akdogan; et al. (European Journal of Applied Physiology, 2024)
Purpose Physical exercise is crucial for healthy aging and plays a decisive role in the prevention of atherosclerotic cardiovascular disease (ASCVD). A higher level of cardiorespiratory fitness (CRF) in the elderly is associated with lower cardiovascular and all-cause mortality. This study investigated the association of CRF level with vascular function and cardiovascular risk factors in the elderly. Methods We examined 79 apparently healthy and physically active subjects aged > 55 years (64 ± 4 years). Cardiovascular functional parameters assessed included brachial and central blood pressure (BP), pulse wave velocity (PWV), augmentation index (Aix), and ankle-brachial index. Sonography of the common carotid artery was performed. CRF level was determined by a cardiopulmonary exercise test, and everyday activity was quantified with an accelerometer. Results All participants had a higher CRF level than the reported age-specific normative values. Twenty-nine subjects had subclinical atherosclerosis of the common carotid artery. Compared with participants without atherosclerosis, they were older ( p = 0.007), displayed higher brachial systolic BP ( p = 0.006), and higher central systolic BP ( p = 0.014). Lower brachial ( p = 0.036) and central ( p = 0.003) systolic BP, lower PWV ( p = 0.004), lower Aix ( p < 0.001), lower body fat percentage (< 0.001), and lower LDL cholesterol ( p = 0.005) were associated with a higher CRF level. Conclusions In this cohort of healthy and physically active individuals, subjects with subclinical atherosclerosis displayed higher systolic brachial and central BP. A higher CRF level was associated with enhanced vascular function, consistent with an influence of CRF on both BP and vascular function in the elderly.

A model for community-driven development of best practices: the Ocean Observatories Initiative Biogeochemical Sensor Data Best Practices and User Guide - Hilary I. Palevsky; Sophie Clayton; Heather Benway; Mairead Maheigan; Dariia Atamanchuk; Roman Battisti; Jennifer Batryn; Annie Bourbonnais; Ellen M. Briggs; Filipa Carvalho; Alison P. Chase; Rachel Eveleth; et al. (Frontiers in Marine Science, 2024)
The field of oceanography is transitioning from data-poor to data-rich, thanks in part to increased deployment of in-situ platforms and sensors, such as those that instrument the US-funded Ocean Observatories Initiative (OOI). However, generating science-ready data products from these sensors, particularly those making biogeochemical measurements, often requires extensive end-user calibration and validation procedures, which can present a significant barrier. Openly available community-developed and -vetted Best Practices contribute to overcoming such barriers, but collaboratively developing user-friendly Best Practices can be challenging. Here we describe the process undertaken by the NSF-funded OOI Biogeochemical Sensor Data Working Group to develop Best Practices for creating science-ready biogeochemical data products from OOI data, culminating in the publication of the GOOS-endorsed OOI Biogeochemical Sensor Data Best Practices and User Guide. For Best Practices related to ocean observatories, engaging observatory staff is crucial, but having a “user-defined” process ensures the final product addresses user needs. Our process prioritized bringing together a diverse team and creating an inclusive environment where all participants could effectively contribute. Incorporating the perspectives of a wide range of experts and prospective end users through an iterative review process that included “Beta Testers’’ enabled us to produce a final product that combines technical information with a user-friendly structure that illustrates data analysis pipelines via flowcharts and worked examples accompanied by pseudo-code. Our process and its impact on improving the accessibility and utility of the end product provides a roadmap for other groups undertaking similar community-driven activities to develop and disseminate new Ocean Best Practices.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Threatened conservation scientists: The aftermath of an eye-opening publication on rewilding - María de las Mercedes Guerisoli; Mauro I. Schiaffini; Pablo Teta; Alejandro E.J. Valenzuela; Patricia Mirol; Javier Nori; Guillermo E. Defossé; María Marcela Godoy; Pablo Krieger; Tomás Withington; María G. Agostini; Christopher B. Anderson; et al. (Biological Conservation, 2023)

Regional differences in the link between water exchange rate across the blood–brain barrier and cognitive performance in normal aging - Valentinos Zachariou; Colleen Pappas; Christopher E. Bauer; Xingfeng Shao; Peiying Liu; Hanzhang Lu; Danny J. J. Wang; Brian T. Gold (GeroScience, 2023)
The blood–brain barrier (BBB) undergoes functional changes with aging which may contribute to cognitive decline. A novel, diffusion prepared arterial spin labeling-based MRI technique can measure the rate of water exchange across the BBB ( k w ) and may thus be sensitive to age-related alterations in water exchange at the BBB. However, studies investigating relationships between k w and cognition have reported different directions of association. Here, we begin to investigate the direction of associations between k w and cognition in different brain regions, and their possible underpinnings, by evaluating links between k w , cognitive performance, and MRI markers of cerebrovascular dysfunction and/or damage. Forty-seven healthy older adults (age range 61–84) underwent neuroimaging to obtain whole-brain measures of k w , cerebrovascular reactivity (CVR), and white matter hyperintensity (WMH) volumes. Additionally, participants completed uniform data set (Version 3) neuropsychological tests of executive function (EF) and episodic memory (MEM). Voxel-wise linear regressions were conducted to test associations between k w and cognitive performance, CVR, and WMH volumes. We found that k w in the frontoparietal brain regions was positively associated with cognitive performance but not with CVR or WMH volumes. Conversely, k w in the basal ganglia was negatively associated with cognitive performance and CVR and positively associated with regional, periventricular WMH volume. These regionally dependent associations may relate to different physiological underpinnings in the relationships between k w and cognition in neocortical versus subcortical brain regions in older adults.

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Current State and Opportunities with Long-acting Injectables: Industry Perspectives from the Innovation and Quality Consortium “Long-Acting Injectables” Working Group - Andrea Bauer; Philippe Berben; Sudhir S. Chakravarthi; Sayantan Chattorraj; Ashish Garg; Betty Gourdon; Tycho Heimbach; Ye Huang; Christopher Morrison; Deepak Mundhra; Ramesh Palaparthy; Pratik Saha; et al. (Pharmaceutical Research, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Ultraconserved elements-based phylogenomic systematics of the snake superfamily Elapoidea, with the description of a new Afro-Asian family - Sunandan Das; Eli Greenbaum; Shai Meiri; Aaron M. Bauer; Frank T. Burbrink; Christopher J. Raxworthy; Jeffrey L. Weinell; Rafe M. Brown; Jonathan Brecko; Olivier S.G. Pauwels; Nirhy Rabibisoa; Achille P. Raselimanana; et al. (Molecular Phylogenetics and Evolution, 2023)

Processing of carbon-reinforced construction materials releases PM2.5 inducing inflammation and (secondary) genotoxicity in human lung epithelial cells and fibroblasts - Jana Pantzke; Arne Koch; Elias J. Zimmermann; Narges Rastak; Svenja Offer; Christoph Bisig; Stefanie Bauer; Sebastian Oeder; Jürgen Orasche; Petra Fiala; Michael Stintz; Christopher P. Rüger; et al. (Environmental Toxicology and Pharmacology, 2023)

Aerosol emissions from a marine diesel engine running on different fuels and effects of exhaust gas cleaning measures - Seongho Jeong; Jan Bendl; Mohammad Saraji-Bozorgzad; Uwe Käfer; Uwe Etzien; Julian Schade; Martin Bauer; Gert Jakobi; Jürgen Orasche; Kathrin Fisch; Paul P. Cwierz; Christopher P. Rüger; et al. (Environmental Pollution, 2023)

Effects of garden management practices, by different types of gardeners, on human wellbeing and ecological and soil sustainability in Swiss cities - Robert Home; Olivia Lewis; Nicole Bauer; Andreas Fliessbach; David Frey; Stéphanie Lichtsteiner; Marco Moretti; Simon Tresch; Christopher Young; Andrea Zanetta; Matthias Stolze (Urban Ecosystems, 2019)

Modelling End-of-Season Soil Salinity in Irrigated Agriculture Through Multi-temporal Optical Remote Sensing, Environmental Parameters, and In Situ Information - Murodjon Sultanov; Mirzakhayot Ibrakhimov; Akmal Akramkhanov; Christian Bauer; Christopher Conrad (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2018)

On-Command Drug Release from Nanochains Inhibits Growth of Breast Tumors - Pubudu M. Peiris; Morgan Tam; Peter Vicente; Aaron Abramowski; Randall Toy; Lisa Bauer; Aaron Mayer; Jenna Pansky; Elizabeth Doolittle; Samantha Tucci; Erik Schmidt; Christopher Shoup; et al. (Pharmaceutical Research, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Somatische Tumormutationen eröffnen neue Therapieoptionen - Christopher Schroeder; Peter Bauer; Falko Fend; Olaf Riess (BIOspektrum, 2014)

Wind‐induced variability in coastal larval retention areas: a case study on Western Baltic spring‐spawning herring - Robert Klaus Bauer; Daniel Stepputtis; Ulf Gräwe; Christopher Zimmermann; Cornelius Hammer (Fisheries Oceanography, 2013)
The investigation of larval dispersal and retention, their variability and dependence on wind conditions, has become a major topic in fisheries research owing to potential effects on stock recruitment and stock structuring. The present study quantifies the wind‐induced variability of larval retention of herring in a highly productive coastal lagoon of the Western Baltic Sea. This lagoon, the Greifswalder Bodden, represents the main spawning area of Western Baltic Spring‐Spawning Herring, a stock that has recently undergone a continuous decline in recruitment. The study tests whether this decline was related to changes in larval retention, more precisely to changes in wind conditions, the main forcing of the lagoon's circulation. To answer this, a model approach was applied. Larvae were tracked as Lagrangian drifters under constant and variable wind conditions, examining the main drift patterns and reconstructing the incidents during the period of recruitment decline. For the latter, weekly cohorts of virtual larvae were released in the lagoon over the entire spawning period (April–June; >16 weeks). The fraction of retained larvae per cohort was related to observed larval abundances. On this basis, a new retention index was defined to evaluate the annual larval retention. The results presented cannot explain the observed recruitment decline but characterize the lagoon as an important larval retention area by virtue of unsteady wind conditions that prevent a steady outflow of larvae.

Product Lifecycle Approach to Cascade Impaction Measurements - Terrence P. Tougas; Dave Christopher; Jolyon Mitchell; Svetlana Lyapustina; Michiel Van Oort; Richard Bauer; Volker Glaab (AAPS PharmSciTech, 2011)

Organic Matter Accumulation and Community Change at the Peatland–Upland Interface: Inferences from 14C and 210Pb Dated Profiles - Ilka E. Bauer; Jagtar S. Bhatti; Christopher Swanston; R. Kelman Wieder; Caroline M. Preston (Ecosystems, 2009)

Haploinsufficiency of PAX9 is associated with autosomal dominant hypodontia - Parimal Das; David W. Stockton; Christopher Bauer; Lisa G. Shaffer; Rena N. D’Souza; Timothy J. Wright; Pragna I. Patel (Human Genetics, 2002)

Biotype of the purple nonsulfur photosynthetic bacterium, Rhodospirillum centenum - David Nickens; Christopher J. Fry; Lisa Ragatz; C. E. Bauer; Howard Gest (Archives of Microbiology, 1996)